THE ASSESSMENT OF THE CHILD AND ADOLESCENT'S NUTRITIONAL AND HEALTH STATUS IN THE NURSE'S CARE PRACTICE - Maria Helena do Nascimento Souza; Gabrielle Silva da Silveira; Átila Ferreira Soares Pinto; Vitória Regina Domingues Sodré; Liane Gack Ghelman (Universidade Federal do Paraná, 2013)
This descriptive, exploratory study aimed to assess the nutritional status of children and adolescents attending an Educational Center in a community in the city of Rio de Janeiro, to identify their principal health problems and to analyze the association between the occurrence of health problems and their nutritional status. Data collection took place with 168 participants, and the results showed that being overweight or obese were the main nutritional disturbances, and problems referent to the respiratory system. There was no statistical difference between nutritional status and health problems. The study confirmed the national tendency of the change in the nutritional profile among children and adolescents. The importance of nurses' educational work in actions directed at health promotion and nutrition in this population is emphasized.